ASYMMETRIC SYNTHESIS OF (R)-S-5-(3'-HYDROXY-4’-IZOAMILOXYBUTYL)-4-ALLYL-1,2,4-TRIAZOL-3-YL-CYSTEINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
An efficient method for asymmetric synthesis of (R)-S-5-(3'-hydroxy-4'-izoamiloxy-butyl)-4-allyl-l,2,4-triazol-3-yl-cysteine via asymmetric Michael addition of heterocyclic thiol’s to the electrophile C=C bond of dehydroalanine in Ni(ll) complex of Shiff's bases by a chiral reagent L-2-N-(N'-benzylprolyl)aminobenzo-phenone with following decomposition of the reaction mixtures and isolation of the resulting amino acids has been developed. 3-(3'-hydroxy-4'-izoamiloxybutyl)-4-allyl-5-mercapto-1,2,4-triazole were used as nucleophiling reagent. Addition results in high stereoselectivity (up to 97%) and good chemical yields. The obtained diastereoisomeric complexes with (S,R)- and (S,S)-absolute configuration were separated on SiO2 and determined by the usual chemical and physical methods. After the mixture of diastereoisomeric complexes had been decomposed in 2 N HCl, optically active ^-substituted of heterocyclic α-cysteine with (R)-absolute configuration and initial chiral reagent with initial optical purity were isolated. Thus (R)-5-5-(3'-hydroxy-4'-izoamiloxybutyl)-4-allyl-l,2,4-triazol-3-yl-cysteine with (R)-absolute configuration in high optical purity (>99%) were synthesized.
Keywords: asymmetric synthesis; Ni(ll) complex of Shiff's bases; dehydroalanine; (R)-absolute configuration